ANALISIS EFEKTIVITAS SISTEM CROWDFUNDING DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT - Riduwansah; Muhammad Farisan Kasyfi; Lili Nur Indah Sari; Al-Amin (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The purpose of this research is to find out how to analyze the effectiveness of the Crowdfunding System in Improving the Economic Welfare of the Community. The method of this research is descriptive, analytical, and critical. Therefore, the author can comprehensively outline how the Analysis of the Effectiveness of the Crowdfunding System in Improving the Economic Welfare of the Community. In this study, the author optimally uses two data sources related to this research, namely. Primary data sources and secondary data sources. The results of this research are that the crowdfunding system has been proven to be effective in providing alternative funding for MSMEs in Indonesia. With stronger regulatory support, increased financial literacy, and good risk management, crowdfunding has great potential to support the growth and sustainability of MSMEs in Indonesia.